Equine infectious anemia affects the athletic performance of equines from the Brazilian Pantanal region - Andrade, Débora Roque de Freitas (2018)
The objective of this work was to evaluate the effects of equine infectious anemia (EIA) on the physical performance of equines from the Brazilian Pantanal region. A total of 16 males were evaluated, divided into two groups: 8 seronegative (G1) and 8 seropositive (G2) for EIA. Two graded exercise tests were carried out before (T1) and after (T2) 42 days of training. Heart rate, lactate concentration, distance covered, and hematocrit level were recorded. In both tests, G1 covered a greater distance. In T2, G2 had lower hematocrit levels and lower speeds reached at different lactate concentrations and heart rates. The athletic performance of the evaluated equines is affected by equine infectious anemia.